AG311, a small molecule inhibitor of complex I and hypoxia-induced HIF-1α stabilization. (1st March 2017) - Bastian, Anja; Matsuzaki, Satoshi; Humphries, Kenneth M.; Pharaoh, Gavin A.; Doshi, Arpit; Zaware, Nilesh; Gangjee, Aleem; Ihnat, Michael A.
Abstract: Cancer cells have a unique metabolic profile and mitochondria have been shown to play an important role in chemoresistance, tumor progression and metastases. This unique profile can be exploited by mitochondrial-targeted anticancer therapies. A small anticancer molecule, AG311, was previously shown to possess anticancer and antimetastatic activity in two cancer mouse models and to induce mitochondrial depolarization. This study defines the molecular effects of AG311 on the mitochondria to elucidate its observed efficacy. AG311 was found to competitively inhibit complex I activity at the ubiquinone-binding site. Complex I as a target for AG311 was further established by measuring oxygen consumption rate in tumor tissue isolated from AG311-treated mice. Cotreatment of cells and animals with AG311 and dichloroacetate, a pyruvate dehydrogenase kinase inhibitor that increases oxidative metabolism, resulted in synergistic cell kill and reduced tumor growth. The inhibition of mitochondrial oxygen consumption by AG311 was found to reduce HIF-1α stabilization by increasing oxygen tension in hypoxic conditions. Taken together, these results suggest that AG311 at least partially mediates its antitumor effect through inhibition of complex I, which could be exploited in its use as an anticancer agent. Highlights: AG311 competitively inhibits ubiquinone-binding to complex I and prevents electron transfer and mitochondrial respiration. Cellular response to hypoxia is reduced by AG311, including HIF-1α protein levels, target genes, and oxygen tension. Combination of AG311 and dichloroacetate augments cytotoxicity and tumor growth reduction.